The Effect of Tracheal Intubation-Induced Autonomic Response on Photoplethysmography - Pekka Talke (Anesthesiology Research and Practice)
Introduction. Intraoperative stress responses and postoperative pain can be monitored using photoplethysmography (PPG). PPG signal has two components, AC and DC. Effects of noxious stimuli-induced stress responses have not been studied on the DC component of PPG. The aim of this study was to investigate the effect of a known noxious stimulus (endotracheal intubation) on both the AC and DC components of PPG. Methods. 15 surgical patients having general anesthesia were enrolled into this clinical study. PPG was recorded electronically from a pulse oximeter. Maximum changes in the AC and DC components of the PPG and pulse rate were determined in response to endotracheal intubation from high frequency (62.5 Hz) PPG recordings. Results. Endotracheal intubation-induced autonomic stress response resulted in a significant decrease in the AC component of the PPG and an increase in pulse rate in every subject (p<0.05 for all). The decrease in the AC component of the PPG was 50±12% (p<0.05) and the increase in pulse rate was 26±10 bpm (p<0.05). The response of the DC component was variable (p = NS). Conclusion. Endotracheal intubation-induced stress response resulted in a significant and consistent change in the AC, but not the DC component of the PPG. This trial is registered with ClinicalTrials.gov Identifier NCT03032939.